(untitled) (CIPEEX, 2022)
CERVICAL ADENOCARCINOMA CORRESPONDS TO A MALIGNANT NEOPLASM THAT ORIGINATES FROM ENDOCERVICAL GLANDS. THE MUCINOUS TYPE CORRESPONDS TO THOSE ADENOCARCINOMAS THAT HAVE THE CAPACITY TO PRODUCE MUCUS. THIS STUDY AIMED TO REPORT THE DIFFERENTIAL TREATMENT CHOSEN FROM A MULTIPROFESSIONAL DISCUSSION FOR ONCOLOGIC PATIENTS WITH RARE URINARY ANATOMICAL VARIATION, ACCORDING TO THEIR ANATOMICAL, PHYSIOLOGICAL AND PERSONAL SPECIFICITIES, AND TO RELATE IT TO THE STANDARD TREATMENT INDICATED FOR THIS SPECIFIC TYPE OF CANCER (MUCINOUS ADENOCARCINOMA OF THE UTERINE CERVIX NIC II, STAGING IB2). A 40-YEAR-OLD PATIENT REPORTS HAVING URINARY TRACT ABNORMALITIES (DUPLICITY OF THE BLADDER AND URETHRA) AND HAVING UNDERGONE MULTIPLE SURGICAL CORRECTIONS OF THE GASTROINTESTINAL TRACT (DUPLICITY OF THE INTESTINE). ADMITTED TO THE HOSPITAL IN AUGUST 2016 DUE TO UTERINE CHANGES FOUND IN POSTERIOR GYNECOLOGICAL EVALUATION. AT SPECULAR EXAMINATION, PROVEN DUPLICITY OF URETHRA, IN ADDITION TO ULCER-INFILTRATIVE LESION WITH MUCINOUS SECRETION OF APPROXIMATELY 4 CM. AT VAGINAL TOUCH, SOFTENED NECK, WITH MOBILE LESION. PELVIC MAGNETIC RESONANCE IMAGING (MRI) AND CONIZATION WERE PERFORMED. ANATOMOPATHOLOGICAL DIAGNOSIS OF CONIZATION DIAGNOSED INVASIVE MUCINOUS ADENOCARCINOMA, STAGED IN IB2. CONSIDERING THE POSSIBILITY OF ADHERENCE DUE TO PREVIOUS SURGICAL ANTECEDENTS AND THE PATIENT’S DESIRE TO MAINTAIN HER FERTILITY, WE CHOSE TREATMENT THROUGH BRACHYTHERAPY WITH ADAPTATIONS, DUE TO THE ANATOMICAL VARIATIONS PRESENT.